Pengaruh Supervisi Akademik Kepala Sekolah Terhadap Kompetensi Pedagogik Guru Di SD Negeri Kecamatan Margadana Kota Tegal - Jayanti, Rowi; Yuliejantiningsih, Yovitha; Prayito, Muhammad (Jayapangus Press, 2025)
This study analyzes the influence of academic supervision of school principals on the pedagogic competence of teachers at SDN Margadana Tegal. Pedagogic competence is focused on the teacher's ability to design, implement, assess, and evaluate learning. The background of the research is based on the low pedagogic competence of teachers identified through initial observation. Teachers still experience obstacles in the preparation of learning tools, the implementation of learning is not as planned, and has limitations in classroom management and the use of teaching aids. The 2024 Teacher Performance Assessment (PKG) shows pedagogic competence as the lowest competence. Education Report Data supports these findings with a decrease in achievement from the